Cometabolic degradation of chloramphenicol via a meta-cleavage pathway in a microbial fuel cell and its microbial community. (April 2017) - Zhang, Qinghua; Zhang, Yanyan; Li, Daping
Highlights: The MFC with acetate as electrons donor increased the removal rate of CAP. The CAP degradation was optimized using Box-Behnken model. Antibacterial activity of CAP was eliminated after treatment by MFC. The electrogenic bacteria enriched in MFC under the closed-circuit mode. Abstract: The performance of a microbial fuel cell (MFC) in terms of degradation of chloramphenicol (CAP) was investigated. Approximately 84% of 50 mg/L CAP was degraded within 12 h in the MFC. A significant interaction of pH, temperature, and initial CAP concentration was found on removal of CAP, and a maximum degradation rate of 96.53% could theoretically be achieved at 31.48 °C, a pH of 7.12, and an initial CAP concentration of 106.37 mg/L. Moreover, CAP was further degraded through a ring-cleavage pathway. The antibacterial activity of CAP towards Escherichia coli ATCC 25922 and Shewanella oneidensis MR-1 was largely eliminated by MFC treatment. High-throughput sequencing analysis indicated that Azonexus, Comamonas, Nitrososphaera, Chryseobacterium, Azoarcus, Rhodococcus, and Dysgonomonas were the predominant genera in the MFC anode biofilm. In conclusion, the MFC shows potential for the treatment of antibiotic residue-containing wastewater due to its high rates of CAP removal and energy recovery.